Insulina y péptido C como indicador de la función β pancreática en pacientes diabéticos tipo II que acuden a la clínica Medihospital - Guamán Cabrera, Nancy Aracely (2023)
Type 2 diabetes mellitus is a disease that affects the endocrine system due to alterations in the metabolism of carbohydrates, resulting in an imbalance in glucose homeostasis and therefore dysfunction in the function of β cells of pancreas. The objective of this curricular integration work was to determine the levels of insulin and C-peptide as indicators of pancreatic β function in type II diabetic patients who attended the Medihospital clinic in the period from November 2022 to February 2023, thanks to the application of non-probabilistic sampling there was a population of 57 patients diagnosed with type 2 diabetes mellitus. Insulin and C-peptide levels were quantified, obtaining normal values for the most part (89.5% and 40.4%). To establish the relationship between insulin and C-peptide levels with the function of pancreatic β cells the HOMA-β index was determined, resulting in 87.7% of patients with poor functionality due to the time of diagnosis or poor management of DM2, resulting in cell failure, loss of pancreatic reserve, and β-cell dysfunction, while 12.3% presented normal β cell function. In addition, insulin and C-peptide levels were related to age, finding a value of p˃0.228 and p˃0.598 respectively when applying the Chi square test, indicating that there is no statistically significant relationship and that age does not influence the alteration or decrease in the levels of the analytes mentioned